Propriedades genéricas de autofunções e autovalores de operadores elípticos na forma divergente em variedades Riemannianas - (:unkn) unknown (Universidade Federal do Amazonas, 2020)
In this work, we prove generic properties of eigenvalues and eigenfunctions to two and to three parameters families of the elliptic operators in the divergence form on compact Riemannian manifolds with boundary. We assume the Dirichlet, T-Neumann and T-Robin boundary conditions. The main tools that we used were developed by K. Uhlenbeck in [Generic Properties of Eigenfunctions, Amer. J. Math. 98 (1976) 1059- 1078].
Keywords: Variedades Riemannianas; Operadores elípticos; Condição de Dirichlet; Condição de T-Neumann; Condição de T-Robin; CIÊNCIAS EXATAS E DA TERRA: MATEMÁTICA; Operadores elípticos; Propriedades genéricas; Condição de Dirichlet; Condição de T-Neumann; Condição de T-Robin